2000
DOI: 10.1046/j.1365-2168.2000.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fistula after pancreatic head resection

Abstract: A standardized technique and a continuing effort to improve perioperative management may be responsible for low mortality and surgical morbidity rates after pancreatic head resection. Pancreatic complications occur with Whipple, PPPD and DPPHR procedures with a similar prevalence. Pancreatic fistula no longer seems to be a major problem after pancreatic head resection and rarely necessitates surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
293
5
24

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(335 citation statements)
references
References 40 publications
13
293
5
24
Order By: Relevance
“…However, the experienced surgeon's overall incidence of clinically relevant pancreatic fistulas was 10.8% in this study, which is a similar rate to what other studies have reported 2, 3, 5. The pancreatic anastomosis technique has been considered to be the most important factor in fistula development 26, 27. Even though secondary operators use the pancreatic anastomosis technique of the experienced surgeon, fine differences in their technique could affect the development of POPF.…”
Section: Discussionsupporting
confidence: 83%
“…However, the experienced surgeon's overall incidence of clinically relevant pancreatic fistulas was 10.8% in this study, which is a similar rate to what other studies have reported 2, 3, 5. The pancreatic anastomosis technique has been considered to be the most important factor in fistula development 26, 27. Even though secondary operators use the pancreatic anastomosis technique of the experienced surgeon, fine differences in their technique could affect the development of POPF.…”
Section: Discussionsupporting
confidence: 83%
“…More studies using the strict definition applied by the International Study Group of Pancreatic Surgery (ISGPS) [3] report that POPF rates vary between 3 % after pancreatic head resection [2,4] and up to 30 % following distal pancreatectomy [5][6][7]. Many risk factors for POPF have been identified, such as gender [8], body mass index (BMI) [9,10], status of the pancreatic parenchyma [11], diameter of the main pancreatic duct (MPD) [12], and kind of disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of POPF after PD is around 5-10 % even in high-volume centres although rates of less than 4 % have been reported [23][24][25]. Most importantly, pancreatic leakage is still responsible for 33-88 % of post-operative deaths after pancreatic resection [26][27][28][29][30].…”
Section: Post-operative Pancreatic Fistula (Popf)mentioning
confidence: 99%